A trojan framework in AES core to evade state-of-the-art HT detection schemes. (May 2021) - Das, Nilanjana; Sen, Riom; Ray, Dwaipayan; Banerjee, Nandini; Halder, Joy; Tenhunen, Hannu; Sikdar, Biplab K.
Abstract: This paper explores cipher-destroying and secret key emitting Hardware Trojan (HT) in Advanced Encryption Standard (AES) cores. It reports a malicious trojan circuit which is implanted in the 10th round of encryption modules to make the AES core vulnerable for system design. Stealthiness of the combinational trojan against the dimension of signal lines, involved to trigger the trojan, is examined. It is shown that such trojans are malicious and hard to detect following the existing trojan detection methodologies. The explored malevolent HT can be the cause of severe damage to a system as it leaks out the secret key to an intruder. An existing trojan detection technique is, therefore, modified to propose seamless detection of such trojans.